Anomia rehabilitation viewed from a pragmaticfunctional paradigm. A case study - Rosell-Clari, Vicent; Hernández-Sacristán, Carlos (Revista de Investigación en Logopedia, 2017)
The aim of this paper is to examine the effects of a therapeutic programme based on a pragmaticfunctional paradigm. Elements of the therapeutic programme have been selected from the heuristic plan established in this paradigm by taking into consideration the particular profile of the individual case under study: a case of anomic aphasia. The phases of the therapeutic programme, administration criteria and the intensity of the therapy have been illustrated and reasoned for this particular case. Two tests have been selected to assess linguistic abilities, administered before and after the therapeutic intervention. One of them is the well-known BDAE (Boston Diagnostic Aphasia Examination) in its Spanish version (Goodglass & Kaplan, 1998), which enables a conventional, standardised assessment of linguistic skills to be carried out. The other is the MetAphAs (Metalanguage in Aphasia Assessment) test (Hernández-Sacristán, Rosell-Clari, Serra-Alegre & Quiles-Climent, 2012; Rosell-Clari & Hernández- Sacristán, 2014), which has been designed to assess natural metalinguistic abilities as representative of the metacognitive dimension of verbal behaviour. After treatment, the patient made progress in all language areas, although retaining mild anomia. The diagnosis changed from motor-mixed aphasia to anomic aphasia according BDAE after 8 months of treatment. The patient also demonstrated meaningful advances in performing different kinds of metalinguistic tasks as measured with the MetAphAs test. The patient’s own reports and reports from family members confirm recovery of a practically autonomous way of life after treatment.
Keywords: Anomia rehabilitation; Aphasia rehabilitation; Conversation-based techniques; Metacognitive abilities; Pragmatic-functional paradigm.